Species composition of coastal dune vegetation in Scotland has proved resistant to climate change over a third of a century. (3rd July 2015) - Pakeman, Robin J.; Alexander, Jim; Beaton, Joan; Brooker, Rob; Cummins, Roger; Eastwood, Antonia; Fielding, Debbie; Fisher, Julia; Gore, Sarah; Hewison, Richard; Hooper, Russell; Lennon, Jack; et al.
Abstract Climate change is expected to have an impact on plant communities as increased temperatures are expected to drive individual species' distributions polewards. The results of a revisitation study after c. 34 years of 89 coastal sites in Scotland, UK, were examined to assess the degree of shifts in species composition that could be accounted for by climate change. There was little evidence for either species retreat northwards or for plots to become more dominated by species with a more southern distribution. At a few sites where significant change occurred, the changes were accounted for by the invasion, or in one instance the removal, of woody species. Also, the vegetation types that showed the most sensitivity to change were all early successional types and changes were primarily the result of succession rather than climate‐driven changes. Dune vegetation appears resistant to climate change impacts on the vegetation, either as the vegetation is inherently resistant to change, management prevents increased dominance of more southerly species or because of dispersal limitation to geographically isolated sites.